A first look back: model performance under Solvency II - Ralf Korn; Gerhard Stahl (European Actuarial Journal, 2023)
We consider an empirical backtesting for the Solvency Capital Required (SCR) under Solvency II. Based on empirical facts that the Basic own Funds (BoF) can be assumed to evolve log-normally and have a much lower volatility than the corresponding equity for our test data, we make a proposal based on Earnings at Risk (EaR) that can be used to reduce the biases from overshooting SCR estimates in a prudential way.
Keywords: 510; Solvency II; Backtesting; Capital requirement